Knowledge and practice of health extension workers on drug provision for childhood illness in west Gojjam, Amhara, Northwest Ethiopia - Ager Befekadu; Mezgebu Yitayal (BMC Public Health, 2020)
Abstract Background The HEP was established decades ago to address preventive, promotive and selective curative services through Health Extension Workers (HEWs). However, knowledge and practice of HEWs on drug provision for childhood illnesses such as diarrhea, fever, and/or acute respiratory infection have not been well studied. This study aimed to assess the knowledge and practice of HEWs on drug provision for childhood illnesses. Methods An institutional-based cross-sectional study was conducted among 389 rural HEWs. The districts were selected by using simple random sampling technique, and all the HEWs in the districts were included in the study. Bivariable and multivariable logistic regressions were performed to see the association between knowledge and practice of HEWs on drug provision with the response variables. Results The study revealed that 57.5 and 66.8% of HEWs had good knowledge and practice on drug provision for childhood illnesses, respectively. Having college diploma (AOR = 5.59; 95% CI: 1.94, 16.11), 7–9 years (AOR = 2.7; 95% CI: 1.3, 5.5) and 10–12 years (AOR = 2.7; 95% CI: 1.4, 5.4) of experiences, being supervised quarterly (AOR = 0.24; 95% CI: 0.13, 0.47) and biannually (AOR = 0.11; 95% CI: 0.04, 0.30), and having national guideline (AOR = 0.22; 95% CI: 0.06, 0.90) were factors significantly associated with good knowledge. In addition, having college diploma (AOR =3.1; 95% CI: 1.1, 8.8), not receiving refreshment training (AOR = 0.31; 95% CI: 0.11, 0.91), being supervised biannually (AOR = 0.32, 95% CI: 0.13, 0.80), and not having national guideline (AOR = 0.16, 95% CI: 0.04, 0.60) were factors significantly associated with good practice. Conclusion The study indicated that a considerable number of HEWs had poor knowledge and practice on drug provision. Socio-demographic factors such as educational status, and work experience; and health systems and support related factors such as training, supervision, and availability of national guidelines, and training had a significant association with HEWs’ knowledge and practice on drug provision. Therefore, designing appropriate strategy and providing refreshment training, and improving supervision and availability of national guidelines for HEWs might improve the knowledge and practice of HEWs on drug provision.